2007
DOI: 10.1007/s10151-007-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effect of sustained inflation and rapid inflation/deflation of the intrarectal balloon upon rectoanal inhibitory reflex parameters in asymptomatic subjects

Abstract: RAIR parameters are influenced by the choice of inflation pattern. Further studies are required to establish a standard intrarectal balloon inflation pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Because the response is invariably triggered with the onset of a need to defecate, we suspect that this must be centrally modulated. Additionally, much like the graded changes in RAIR (12,22), the SMR also exhibits a larger response at higher volumes of rectal distention (5). Supra spinal and parasympathetic pathways are implicated in the modulation of RAIR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the response is invariably triggered with the onset of a need to defecate, we suspect that this must be centrally modulated. Additionally, much like the graded changes in RAIR (12,22), the SMR also exhibits a larger response at higher volumes of rectal distention (5). Supra spinal and parasympathetic pathways are implicated in the modulation of RAIR.…”
Section: Discussionmentioning
confidence: 98%
“…RAIR is an enteric neuronal reflex that is mediated by nitric oxide, vasoactive intestinal peptide, and adenosine triphosphate and causes relaxation of internal anal sphincter (IAS) (18). The rate and method of rectal distention (intermittent vs. ramp) affect the properties of the RAIR, and this reflex response is classically absent in Hirschsprung's disease and other conditions such as after circular rectal myotomy and after lower anterior resection (4,12,22).…”
mentioning
confidence: 99%
“…Similar technical factors are likely to influence EAS EMG activity during deflation suggesting that caution should be adopted in the acceptance of a 'deflation reflex' as advocated by Shafik as a measure of anorectal functional disturbance [121]. This approach has recently been corroborated by Monteiro et al who have confirmed that parametric observations of rectoanal inhibition during inflation/deflation cycles are highly operator-/technique-dependent [122].…”
Section: Anal and Perineal Reflexesmentioning
confidence: 83%
“…Diese Konzeption Shafiks schafft einige Verwirrung in Bezug darauf, was eine stimulierende rektale Dehnung darstellt, die imstande ist, einen rektoanalen Stimulus hervorzurufen [112][113][114], wenn ein ungehemmtes rektales Detrusor-"Syndrom" als eine "Ursache" von Stuhlinkontinenz vorliegt [115,116]. von der Untersuchungstechnik abhängen [122]. Dies ist teilweise ein Charakteristikum der exzessiven rektalen Füllung, bei der der EAS sich mit dem Risiko (oder der Realität) des Stuhlverlusts während des Vorgangs zusammenzieht [118][119][120].…”
Section: Anale Und Perineale Reflexeunclassified